Radiographic Examination of Alveolar Ridge Resorption in Relation to Age in Kennedy Class II Edentulism - Serkan Yılmaz; Özden Melis Durmaz Yılmaz; Emin Murat Canger (European Annals of Dental Sciences)

(untitled)
Purpose: After the loss of teeth, alveolar bone begins to resorb due to disappearance of the stimulus being applied by the teeth to the alveolar bone. This situation is termed as residual ridge resorption. The aim of this study is to determine the amount of alveolar bone resorption occured in the maxilla and mandible of the patients having Kennedy Class II edentulousness and the distribution of it according to age groups. Material and Methods: The study was carried out on the panoramic radiographs of 122 individuals (60 mandible, 62 maxilla). Vertical measurements were made at 10 sites (central incisors, first premolars and molars at the left and right of both jaws). The difference of the measurements according to the group and demographic variables was analyzed with the independent groups independent-t and one-way ANOVA tests. Also, dentate and edentulous measurements according to the group and demographic characteristics in the group interaction was analyzed with the repeated ANOVA test. Results: When the edentulous regions were considered, the vertical height values of the mandible were lower than maxilla. Also, statistically significant difference was detected in the maxillar premolar region of the edentulous regions. According to gender, womens’ vertical height results were found to be lower than men and the vertical heights of the 6-12 months group were higher than 12-24 months group. Conclusions: According to these results, we think that the patient should be directed to implant rehabilitation in order to prevent bone loss, especially in edentulous patients in the maxillary premolar region.